A pH‐induced, intein‐mediated expression and purification of recombinant human epidermal growth factor in Escherichia coli. (10th April 2015) - Zhang, Yuejuan; Zhang, Kun; Wan, Yi; Zi, Jing; Wang, Yan; Wang, Jun; Wang, Lili; Xue, Xiaochang
<x xml:space="preserve">Abstract</x> Human epidermal growth factor (hEGF) is a cellular factor that promotes cell proliferation and has been widely used for the treatment of wounds, corneal injuries, and gastric ulcers. Recombinant hEGF (rhEGF) has previously been expressed using the pTWIN1 system with pH‐induced intein and a chitin‐binding domain. The rhEGF protein can be purified by chitin affinity chromatography because of the high affinity between the chitin‐binding domain fusion‐tag and the column. However, uncontrolled cleavage presents a major problem with this method. To overcome this problem, a novel purification method has been developed for a pH‐induced intein tag rhEGF that is expressed in Escherichia coli. Following purification by denaturation of inclusion bodies, the fusion protein is renatured and simultaneously induced to self‐cleave by dialysis. Further purification of rhEGF is achieved by heat treatment and ion‐exchange chromatography. Our results show that the purity of rhEGF obtained through this method is over 98% and the quantity of purified rhEGF is 248 mg from a 1 L culture or 2, 967 mg from a 12 L culture. Therefore, we conclude that we have developed an efficient purification method of rhEGF, which may be used for the purification of other heat‐resistant and acid‐resistant recombinant proteins. © 2015 American Institute of Chemical Engineers Biotechnol. Prog., 31:758–764, 2015